First total synthesis of (5Z,9Z)-(±)-2-methoxy-5,9-octadecadienoic acid, a marine derived methoxylated analog of taxoleic acid - Carballeira, Néstor M. (2008)
The first total synthesis for the sponge derived (5Z,9Z)-(±)-2-methoxy-5,9-octadecadienoic acid, an analog of taxoleic acid, was accomplished in seven steps and in a 10% overall yield. It was again corroborated that the best strategy to prepare these cis,cis dimethylene interrupted double bonds is the double-alkyne bromide coupling reaction of 1,5-hexadiyne, which provides the advantage of achieving a 100% cis stereochemical purity for both double bonds after hydrogenation under Lindlar conditions. The α-methoxy functionality was best prepared via the Mukaiyama reaction of (4Z,8Z)-heptadecadienal with trimethylsilyl cyanide and triethylamine followed by acid hydrolysis. Selective methylation of the hydroxyl group of (5Z,9Z)-(±)-2-hydroxy-5,9-octadecadienoic acid was achieved with sodium hydride/methyl iodide when tetrahydrofuran was used as solvent. Complete spectral data is presented, for the first time, for this unusual marine α-methoxylated fatty acid.